2020
DOI: 10.3390/ijms21207524
|View full text |Cite
|
Sign up to set email alerts
|

p38β and Cancer: The Beginning of the Road

Abstract: The p38 mitogen-activated protein kinase (MAPK) signaling pathway is implicated in cancer biology and has been widely studied over the past two decades as a potential therapeutic target. Most of the biological and pathological implications of p38MAPK signaling are often associated with p38α (MAPK14). Recently, several members of the p38 family, including p38γ and p38δ, have been shown to play a crucial role in several pathologies including cancer. However, the specific role of p38β (MAPK11) in cancer is still … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 118 publications
(138 reference statements)
0
25
0
Order By: Relevance
“…While four p38 isoforms exist, the demonstrated effect of p38α‐ and p38β‐specific inhibitors in our study suggests that p38α and p38β play a dominant role in the MAPKi‐induced CD73 upregulation. Both p38α and p38β can be activated by the same MAP2K isoform (MKK6) and have redundant functions and also activate similar downstream kinases [ 36 ]. In addition, an inhibitor targeting only p38α (ralimetinib) and knockdown of p38α (MAPK14) showed no or modest effects, suggesting that both p38α and p38β are involved in the upregulation of CD73, and when p38α is inhibited, p38β continues to drive the signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…While four p38 isoforms exist, the demonstrated effect of p38α‐ and p38β‐specific inhibitors in our study suggests that p38α and p38β play a dominant role in the MAPKi‐induced CD73 upregulation. Both p38α and p38β can be activated by the same MAP2K isoform (MKK6) and have redundant functions and also activate similar downstream kinases [ 36 ]. In addition, an inhibitor targeting only p38α (ralimetinib) and knockdown of p38α (MAPK14) showed no or modest effects, suggesting that both p38α and p38β are involved in the upregulation of CD73, and when p38α is inhibited, p38β continues to drive the signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, p38 can both sensitize some tumor types to chemotherapy and facilitates resistance in others, where p38 inhibition may be beneficial in therapeutic approaches [ 136 , 176 , 177 , 178 ]. Of note, p38 MAPK activity and increased expression have been linked to the progression of breast cancer, prostate cancer, bladder cancer, liver cancer, lung cancer, thyroid cancers, leukemia, and many more [ 35 , 135 , 179 , 180 ]. In solid tumor biology, the p38 MAPK pathway has been shown to promote tumor cell survival and angiogenesis during periods of hypoxia, reoxygenation, and nutrient deficiency by inducing expression of metalloproteinases and vascular endothelial growth factor A (VEGFA) [ 135 ].…”
Section: Pathophysiological Implications Of Mkk3/6-dependent P38 Mapksmentioning
confidence: 99%
“…However, it has been shown that this isoform may also have oncogenic activities, mediated by its implication in the development of important processes of cancer development and prognosis, such as invasion, proliferation, angiogenesis, and inflammation [ 10 ]. On the other hand, p38γ and p38δ isoforms have been recently shown to play a crucial role in several diseases, including cancer [ 63 ], although the role of p38β is not yet fully known [ 64 ].…”
Section: Role Of the P38 Mapk Pathway In Cancermentioning
confidence: 99%
“…However, increased levels of phosphorylated p38α have also been correlated with malignancy in several types of cancer such as thyroid cancer [ 95 ]. As with p38α, p38β may also have a dual function in cancer, playing a role as a tumor suppressor, although more studies are needed to reach a firm conclusion [ 64 ].…”
Section: Role Of the P38 Mapk Pathway In Cancermentioning
confidence: 99%